SOCIO-DEMOGRAPHIC CHARACTERISTICS OF TRAFFIC OFFENDERS - Aleksandra Petrović; Miloš Pljakić; Boško Matović (Pravo)
The human factor is regarded as the most significant element in traffic safety. Its complexity and impact on delinquent traffic behavior bring this issue into focus, especially in developing countries. In criminological studies of the causes of traffic delinquency, it is crucial to identify the personality traits of traffic participants that lead to behaviors deviating from socially desirable norms. In other words, it is necessary to point out those characteristics of traffic participants (personality traits, demographic characteristics, attitudes, habits) that contribute to socially deviant behavior and the commission of traffic offenses. The importance of studying these characteristics lies in their application to find adequate measures to influence the behavior of traffic participants and prevent traffic delinquency. This paper analyses the socio-demographic characteristics of traffic offenders in the Republic of Serbia (age, education level and marital status), based on statistical data on traffic offenses for the period 2010- 2019. These characteristics are essential for understanding the social and  demographic structure and specific social peculiarities of traffic offenders. Numerous studies have shown that socio-demographic characteristics are significantly positively correlated with safe road user behavior. The results of this research on the socio-demographic characteristics of traffic offenders in Serbia for the period 2010–2019 confirm this conclusion, which is presented in this paper.